The good, the bad, and the fuzzy - Scroggs, Kirk (Scroggs, Kirk. Tales of a sixth-grade muppet, 2012)
Targeted by the biggest bully in school after transforming into a Muppet, Danvers Blickensderfer, the star of Kermit's upcoming band camp movie musical, explores a theory that he has also become a superhero with powers he has yet to discover.